Two Food Waste By-Products Selectively Stimulate Beneficial Resident Citrus Host-Associated Microbes in a Zero-Runoff Indoor Plant Production System - Pagliaccia, Deborah; Bodaghi, Sohrab; Chen, Xingyu; Stevenson, Danielle; Deyett, Elizabeth; De Francesco, Agustina; Borneman, James; Ruegger, Paul; Peacock, Beth; Ellstrand, Norman; Rolshausen, Philippe Eric; Popa, Radu; et al. (Frontiers in Sustainable Food Systems, 2020)
The global production of food waste is a far-reaching problem with sizable financial, ethical, social, and environmental costs. Over 66 million tons of food waste is produced annually in the US alone. This waste can be converted into valuable digestate by-products that promote a circular economy within agri-food systems. The present work investigated the use of two liquid digestates of microaerobic fermentation from mixed food waste and beer mash, respectively, as biostimulants for non-bearing citrus plants (nursery stock) grown in a zero-runoff greenhouse system with recirculating irrigation. The digestates’ impact on the structure and diversity of the microbiota was determined on the irrigation water, soil, leaves, roots, and rhizosphere of citrus plants. A combination of culture-dependent (selective media) and culture-independent approaches (Next-Generation Sequencing) was used to assess the composition of the microbial communities and to single out the presence of foodborne pathogens. Our results suggest that the use of digestates is safe (i.e., no human or plant pathogens were present in the digestates or enriched in the plant production system following amendments). Digestates application to the irrigation water reduced the bacterial diversity within 24-48 hours and selectively and significantly stimulated beneficial resident host-associated microorganisms (Pseudomonas putida) by two to three orders of magnitude. Carbon dynamics were analyzed in the nutrient solutions by measuring dissolved organic carbon and characterizing carbon species through gas chromatography-electron ionization-mass spectrometry (GC/EI-MS). Our results indicate that dissolved organic carbon in the recirculating irrigation water spikes after each digestate amendment and it is quickly metabolized by bacteria, plateauing 24 hours after application. Soil carbon, nitrogen, and nutrient dynamics were also analyzed, and results suggest that digestates increased the concentration of some plant nutrients in soils without causing a surge of potentially toxic elements. This study represents a proof-of-concept for the safe re-use of organic wastes, from farming and consumers, in agriculture. Implementing this type of integrated plant production system could reduce the environmental impact of food waste and benefit the public by improving soil health, reducing agricultural footprint, and increasing crop fitness by deploying a method based on a circular economy and sustainable food production approaches.